Effects of an integrative neuromuscular training protocol vs. FIFA 11+ on sprint, change of direction performance and inter-limb asymmetries in young soccer players. Issue 1 (February 2022) - Arede, Jorge; Fernandes, John; Moran, Jason; Leite, Nuno; Romero-Rodriguez, Daniel; Madruga-Parera, Marc
This study compared the effects of integrative neuromuscular training (INT) versus FIFA 11+ protocols on sprint, change of direction performance and inter-limb asymmetries. Thirty young (U-11) male soccer players (age: 11.2 ± 0.7 years; height: 145.6 ± 6.8 cm; body mass: 72.5 ± 3.0 kg) were randomly assigned to each training group, which consisted of two sessions/week for a period of 6-weeks. The INT consisted of play-based tasks designed according to structured training principles, whereas the FIFA 11+ followed standard procedures. Before and after the intervention, 0-20 sprint time and double 180° change of direction test were measured from which change of direction deficit and inter-limb asymmetries were also computed. Significant improvements were found in double 180° change of direction test and deficit for both legs in both groups (all p  < 0.01). A significant decrease was observed in 0-20 sprint time ( p  < 0.05), and inter-limb asymmetries for FIFA 11+ group. A significant group-by-time effect, which favored the FIFA 11+ group, was observed on double 180° change of direction in right leg (F = 15.08, p  < 0.01, η 2 p  = 0.35), but also in change of direction deficit in right (F = 214.19, p  < 0.01, η 2 p  = 0.88), and left legs (F = 126.79, p  < 0.01, η 2 p  = 0.82). These findings suggest youth soccer practitioners should select the FIFA 11+ program to improve inter-limb asymmetries and 0-20 sprint time, and that both training methods are suitable to improve 180° change of direction performance.